Ultrasound‒Mediated Synthesis of High‒Molecular Weight Polystyrene‒Grafted Silver Nanoparticles by Facile Ligand Exchange Reactions in Suspension. Issue 1 (27th August 2013) - Pletsch, Holger; Peng, Ling; Mitschang, Fabian; Schaper, Andreas; Hellwig, Michael; Nette, David; Seubert, Andreas; Greiner, Andreas; Agarwal, Seema
Abstract Ultrasound mediated facile ligand exchange method in suspension for the formation of polystyrene‒grafted silver nanoparticles is reported. Amazingly, this method allows even grafting of very high molecular weight polystyrenes (up to 217 200 g mol−1) having a single terminal thiol group at the chain end. Detailed studies are carried out to gain insights in the role of molecular weight of the ligands and the mechanism of the ligand exchange reactions. Key factors are determined to be the droplet formation by ultrasonification and low silver content, which enhances the availability of the terminal thiol end group significantly. The extraordinary compatibility of the ligand exchange method in particular regarding high molecular weights is attributed to hydrophilic orientation of the terminal thiol groups at the liquid‒liquid interphase. This is proved conclusively by using an in situ method as a reference approach in which agglomeration occurs at considerably lower molecular weights due to the absence of preferred end group orientation within the polymer coil. In homogeneous phase only the chain length is found to be the crucial factor in stabilization of silver nanoparticles.